Peran Kepemimpinan Instruksional Kepala Sekolah dalam Mengatasi Dilema Manajemen Waktu Pembelajaran Aktif di SMP N 6 Panyabungan - Fittin Nurhaliza; Putri Damayanti; Mhd. Hatta; Mhd. Daswar; Kasman Kasman (CV. ALIM'SPUBLISHING, 2026)
The implementation of active learning models such as Problem-Based Learning (PBL) and Project-Based Learning (PjBL) at the junior high school level is often constrained by the complexity of instructional time management. This study aims to examine the role of the principal’s instructional leadership in addressing time management dilemmas in the implementation of active learning at SMP Negeri 6 Panyabungan. A qualitative approach with a descriptive method was employed in this study. Data were collected through non-participant observation and in-depth interviews with key informants, namely the school principal and an Islamic Religious Education (PAI) teacher selected as representatives of field conditions. The findings reveal three main results. First, teachers’ time management constraints are caused by weak control of learning activity transitions, noisy classroom conditions during group division, and low initial student learning readiness. Second, the principal implemented several concrete interventions, including the adoption of block scheduling, clinical supervision focused on classroom management, and the optimization of the Subject Teacher Forum (MGMP) or school learning community. Third, these interventions improved teachers’ instructional efficiency, strengthened classroom activity control, and created a more structured active learning process. However, sustainability challenges remain, particularly resistance from senior teachers who tend to prefer conventional teaching methods. This study concludes that adaptive and solution-oriented instructional leadership is a key factor in addressing the complexity of time management constraints in active learning implementation.